Decision-making process of breastfeeding behavior in mothers with gestational diabetes mellitus based on health belief model - Pan Qian; Lixia Duan; Rujiao Lin; Xiwang Du; Dan Wang; Tieying Zeng; Chenxi Liu (BMC, 2023)
Abstract Background Gestational diabetes mellitus (GDM) threatens GDM mothers and their offspring's health and breastfeeding is one of the most effective ways to decrease the risk. However, the prevalence of breastfeeding among GDM mothers is far from optimal and how GDM mothers develop their feeding behavior is still unclear. Thus, this study aimed to explore the formation of GDM mothers' breastfeeding behaviors based on the health belief model (HBM). Methods A questionnaire survey was conducted on 324 GDM mothers who have given birth within 6 months from January 1 to February 6, 2022. According to HBM, GDM mothers' knowledge, the perceived threat from GDM, the perceived value of breastfeeding, self-efficacy, social support and GDM mothers' breastfeeding behavior were measured. Exclusive breastfeeding (EBF) was defined as an infant who received only breast milk in the past 24 h before the survey. Structural equation modeling (SEM) was applied to explore how GDM mothers form their breastfeeding behaviors based on HBM. Results The prevalence of EBF among GDM mothers was 33.95%. GDM mothers had limited knowledge of GDM (average 63.14% correct answer to 7 questions), especially poor on the long-term effect of GDM (39.81%) and protective effect of breastfeeding (34.57%-45.99%). Although GDM mothers showed high perceived benefits (Mean: 3.35, SD: 0.46), high self-efficacy (Mean: 3.43, SD: 0.97) and high level of social support for breastfeeding (Mean: 3.74, SD: 0.74), the various barriers (Mean: 2.20, SD: 0.47) hindered their success in EBF. The SEM results showed that a higher level of social support and more self-efficacy of breastfeeding resulted in a higher likelihood of EBF, while the higher level of knowledge of GDM, perceived higher barriers and benefits of breastfeeding and higher susceptibility to GDM consequences led to less EBF. Conclusion To promote EBF, physicians' education, emphasizing the protective effect of breastfeeding and how to correct breastfeeding, is highly recommended. In addition, social support for GDM mothers is also important to reduce their barriers to breastfeeding and help enhance self-efficacy in breastfeeding.